Peripheral quantitative computed tomography (pQCT) bone measurements in children with cystic fibrosis. Issue 1 (9th November 2015) - Bai, Wei; Binkley, Teresa L.; Wallace, James W.; Carver, Terrence W.; Specker, Bonny L.
Summary: Background: Individuals with cystic fibrosis (CF) have low bone density and increased fracture risk. Methods: Cross‐sectional study investigating whole body bone mineral content (WBBMC), bone geometry and strength in 12 children with CF compared to 23 age‐ and sex‐matched controls with and without adjusting for age, height, and body composition. Results: CF group had lower WBBMC than controls ( P = 0.007) with larger differences at older ages (age‐by‐group, P = 0.08). CF group had decreased height ( P = 0.006), a trend of lower lean mass per height ( P = 0.08), and no difference in relationship between WBBMC and lean mass compared to controls ( P = 0.65). Periosteal and endosteal circumferences were smaller in CF (each, P = 0.02). Positive relationships of cortical area and bone strength with age were attenuated with CF (group‐by‐age; each, P < 0.01). Conclusion: Children with CF have similar WBBMC relative to lean mass as controls. Cortical bone area and bone strength were less in CF group compared to controls, with greater differences in older children.Pediatr Pulmonol. 2016;51:28–33. © 2015 Wiley Periodicals, Inc.